2018
DOI: 10.1002/ijop.12479
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and risk preferences: Predicting risk behaviour across decision domains

Abstract: Risk-taking is a critical health factor as it plays a key role in several diseases and is related to a number of health risk factors. The aim of the present study is to investigate the role of alexithymia in predicting risk preferences across decision domains. One hundred and thirteen participants filled out an alexithymia scale (Toronto Alexithymia Scale-TAS-20), impulsivity and venturesomeness measures (I7 scale), and-1 month later-the Cognitive Appraisal of Risky Events (CARE questionnaire). The hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Trait-impulsivity was assessed with the 19 dichotomous (yes/no) items of the impulsiveness subscale of the I 7 impulsiveness-venturesomeness-empathy scale (39). We used the Italian adaptation of the I 7 (40,41), and the Cronbach's α was 0.79.…”
Section: Methodsmentioning
confidence: 99%
“…Trait-impulsivity was assessed with the 19 dichotomous (yes/no) items of the impulsiveness subscale of the I 7 impulsiveness-venturesomeness-empathy scale (39). We used the Italian adaptation of the I 7 (40,41), and the Cronbach's α was 0.79.…”
Section: Methodsmentioning
confidence: 99%
“…Alexithymia, which is a personal trait characterized by the inability to identify and describe emotions, 31 may account for this result. Indeed, previous studies have indicated an association between alexithymia and sexual risk taking: 32 , 33 people unable to identify their own feelings and behavioral antecedents could be more likely to unintentionally expose themselves to dangerous situations, then also increasing the probability of contracting STIs. Despite this possible explanation, it is worth noting that a consistent part of the sample selected the “I don't know” response.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a propensity for engaging in risky behaviors may be less likely to adhere to provider recommendations about abstinence from certain substances. Panno et al. (2019) reported that alexithymia was predictive of risk preferences such as aggressive behavior and irresponsible academic or occupational behavior.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) reported that alexithymia was predictive of risk preferences such as aggressive behavior and irresponsible academic or occupational behavior. The EOT aspect of alexithymia was specifically associated with risky sexual behaviors and heavy alcohol use (Panno et al., 2019). The connection between alexithymia and risk preferences provides additional evidence for the importance of early intervention when patients present with alexithymic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation